2020
DOI: 10.1007/s00216-020-02557-0
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput dielectrophoretic filtration of sub-micron and micro particles in macroscopic porous materials

Abstract: State-of-the-art dielectrophoretic (DEP) separation techniques provide unique properties to separate particles from a liquid or particles with different properties such as material or morphology from each other. Such separators do not operate at throughput that is sufficient for a vast fraction of separation tasks. This limitation exists because high electric field gradients are required to drive the separation which are generated by electrode microstructures that limit the maximum channel size. Here, we inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 36 publications
3
44
0
Order By: Relevance
“…Lorenz et al. describes a new type of particle separation technique that involves DEP‐enhanced filtration allowing for the retention and release of sub‐micron particles [110]. Here, they used open porous microstructures consisting of ceramic filters/glass beads as a filter material sandwiched between electrodes.…”
Section: Synthetic Nanoparticlesmentioning
confidence: 99%
“…Lorenz et al. describes a new type of particle separation technique that involves DEP‐enhanced filtration allowing for the retention and release of sub‐micron particles [110]. Here, they used open porous microstructures consisting of ceramic filters/glass beads as a filter material sandwiched between electrodes.…”
Section: Synthetic Nanoparticlesmentioning
confidence: 99%
“…Naturally, aqueous media are preferred in many applications due to a higher flexibility. A possible bridge over the throughput gap might lie in aqueous DEP filters [81] which give promising results for selective particle capture at high throughput. The high selectivity and controllability of DEP filtration could allow more flexible applications compared to conventional industrial separation methods.…”
Section: Discussionmentioning
confidence: 99%
“…We further employed monolithic mullite foams with median pore window diameters from 180 to 270 µm ( Fig. 6B and D), and demonstrated that DEP filtration can effectively separate polystyrene and graphite particles of different sizes (0.5, 3, and 4.5 µm) from aqueous medium at high volumetric flow rates from 1 to 9 mL/min [81]. Applying 600 V rms at 15 kHz, we achieved separation efficiencies between 60 and 100% depending on throughput for 500 nm polystyrene particles.…”
Section: Dep Filtrationmentioning
confidence: 99%
See 2 more Smart Citations